Mergers and acquisitions (M&AS) by R&D intensive firms - Shantanu Dutta; Vinod Kumar (Journal of Risk and Financial Management, 2009)
In this study, we evaluate the impact of R&D intensity on acquiring firms' abnormal returns by examining 925 Canadian completed deals between 1993 and 2002 that have information on R&D expenditures. While examining the returns to acquiring firm shareholders in the R&D intensive firms we evaluate two competing hypotheses: 'growth potential hypothesis' and 'integration failure hypothesis'. According to the 'growth potential hypothesis', in light of the growth potential of the targets acquired by R&D intensive firms, investors are likely to react positively. 'Integration failure hypothesis' focuses on integration difficulties of a target by an R&D intensive firms and suggests that investor might be skeptical of such acquisitions and react negatively. Our results show that R&D intensity (i.e. R&D expenditure by sales) has a positive and significant effect on cumulative abnormal returns of the acquiring firms around the announcement dates. This implies that market generally favors the M&A deals by R&D intensive firms. An analysis of the differentiating characteristics reveal that R&D firms have a significantly higher growth potential and undertake more stock financed deals compared to the non R&D firms. Further, our results show that there is no significant change in long-term operating performance subsequent to the M&A deals for both R&D firms and non R&D firms. In general, our results show support for 'growth potential hypothesis'.
Keywords: G14; G34; 330; Mergers and Acquisitions; R&D intensity; Abnormal returns; Long-term performance